Magnetic Spectrometer Calibration for Gamma-Ray Intensities - Staveley, Anne (My University, 1961)
A study has been made of the external conversion spectrum of gamma-rays of less than 200 kev. A set of semi-empirical curves relating the photoelectric peak height to the gamma-ray intensity has been established using antimony radiators. These results will be discussed. A method of preparing thin beta sources will also be described.
Keywords: gamma-rays; gamma-ray; gamma-ray intensities; magnetic spectrometer; spectrometer; magnetic spectrometer calibration